Evaluating Factors Influencing Auditor Switching: Insights from Indonesian Manufacturing Firms - Siregar, Ernisa; Akbar, Taufiq; Lanjarsih, Laela (West Science Accounting and Finance, 2025)
Audit switching, or the replacement of a public accounting firm by a company, plays a critical role in ensuring audit independence and the reliability of financial reporting. In the manufacturing sector, which significantly contributes to Indonesia’s GDP, audit quality is especially crucial due to the complexity and public exposure of operations. This study employs a purposive sampling method to select a sample of 85 manufacturing firms listed in Indonesia, observed over a three-year period from 2021 to 2023, resulting in a total of 255 observations. Using a quantitative approach, this research aims to address inconsistent findings in previous studies and fill existing gaps in the literature. The results reveal that audit fee, audit opinion, and public accounting firm (PAF) size do not significantly influence the likelihood of auditor switching, as these factors are often perceived as marginal or standardized by management. However, audit tenure shows a significant positive effect, suggesting that longer audit relationships may raise concerns regarding auditor independence and objectivity. Consequently, audit tenure emerges as a key determinant in auditor switching decisions, highlighting its role in maintaining the credibility and integrity of financial audits.